Analisis Penerapan Activity Based Costing (ABC) dalam Penentuan Harga Pokok Produksi pada Coffe Shop Milenial Pancur Batu - Kristina Loryanna Marpaung; Linda Lores (J-CEKI : Jurnal Cendekia Ilmiah, 2024)
This research aims to determine "Analysis of the Application of Activity Based Costing (ABC) in Determining the Cost of Goods Production at the Pancur Batu Millennial Coffee Shop". The calculation of the cost of production for the Millennial Pancur Batu Coffee Shop is by adding up all fixed costs and variable costs. The Traditional System uses the number of units produced as the basis for calculating the Cost of Goods Production. With the Traditional System, the calculation results for the Cost of Goods Production per unit are IDR 35,370. Cost of Goods Production using the Activity-Based Costing System at the Pancur Batu Millenial Coffee Shop. Determination of the Cost of Goods Production based on the Activity-Based Costing System consists of two stages, namely the first stage procedure and the second stage procedure. The Activity-Based Costing System uses more Cost Drivers, therefore the Activity-Based Costing System is able to determine more accurate results and does not cause cost distortion. Apart from that, the Activity-Based Costing System can improve the quality of decision making can't help management improve its strategy planning.